Does managerial bias pose destructive impact on company? A non-linear relationship between CEO’s overconfidence and company value - Bayu Wiratama; Kris Brantas Abiprayu; Siti Ridloah (Diponegoro International Journal of Business, 2018)
This research aims at testing the influence of CEO’s Overconfidence (KDB) on the values of companies registered with the Indonesian Stock Exchange in the period 2007-2015. KDB is a bias inherent in individual, particularly corporate CEO resulted from his/her great authority. A CEO with KDB will assume that his/her company has investment opportunities in the future and, thus, reduce dividend in anticipation of acquiring an investment opportunity in the future. Some opinions argue that KDB’s benefit will be maximal when the confidence is at moderate level. A manager is deemed able to contribute to his/her company, have a good innovation level, have optimal motivation level, and present lower level of cost of debt or capital and optimal amount and rate of investment return. Too low or too high KDB is deemed only to pose negative impact on company value as resulted from non-optimal degree of leverage and investment.